2010
DOI: 10.1590/s1519-38292010000300009
|View full text |Cite
|
Sign up to set email alerts
|

Cuidado humanizado no pré-natal: um olhar para além das divergências e convergências

Abstract: OBJETIVOS: compreender os significados do cuidado humanizado no pré-natal, as divergências, convergências e barreiras para sua efetivação na ótica de gestantes e profissionais. MÉTODOS: pesquisa qualitativa, exploratória, com 19 gestantes e 23 profissionais do ambulatório do Hospital Universitário e de uma unidade básica de saúde, guiada por pressupostos de Edgar Morin e interpretada pela hermenêutica dialética. Os dados foram coletados mediante entrevistas e observação participante. RESULTADOS: destacam-se co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
39

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 12 publications
0
11
0
39
Order By: Relevance
“…In a study based on interviews with pregnant women and health care professionals, Zampieri & Erdmann 34 , reported that educational practices and home visits are considered humanized actions by pregnant women.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study based on interviews with pregnant women and health care professionals, Zampieri & Erdmann 34 , reported that educational practices and home visits are considered humanized actions by pregnant women.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
“…Besides good quality prenatal care, humanized care is the first step towards a healthy birth and a healthy and safe pregnancy 34 . Accordingly, it is worth highlighting the important role of nutritional education as a way to promote individuals' autonomy and comprehensive care 28 .…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%
“…In addition, it reinforces the vital role of researchers to cooperate in the recognition of the advances that contribute to care qualification (4) . In addition, there is the existence of a gap in attention to pregnancy and childbirth related prenatal consultations in primary care (5) . Since they were characterized by a focus on procedures and routines, leaving sharing knowledge and experiences of women in the background, the role of care itself was weakened.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the care of women and their families should be longitudinal, respecting each stage of pregnancy and its significance in their life (5) .…”
Section: Introductionmentioning
confidence: 99%
“…However, recent advances in maternal care have allowed these women to experience motherhood [3]. The coexistence of pregnancy and diabetes Mellitus is an example, and nutritional care for this condition is the subject of this study [2,4].…”
Section: Introductionmentioning
confidence: 99%